2017
DOI: 10.1002/jsfa.8645
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma‐irradiation on cotyledon cell separation and pectin solubilisation in hard‐to‐cook cowpeas

Abstract: As the cell wall changes brought about by gamma-irradiation were associated with pectin solubilisation, this supports the phytate-phytase-pectin theory as a major cause of the HTC defect. However, the non-reversal of the defect in HTC susceptible cowpeas and the absence of an effect on CSP indicate that other mechanisms are involved in HTC defect development in cowpeas, possibly the formation of alkali-soluble, ester bonded pectins. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This phenomenon might be attributed to hard-to-cook defect (Coelho et al, 2007;Jombo, Minnaar, & Taylor, 2017;Martín-Cabrejas et al, 1997). Several theories have been proposed to explain the hard-to-cook phenomenon, including phytase-phytate-pectin theory, lignification theory, protein and starch interactions, and a multiple mechanism theory, but the "phytase-phytate-pectin" theory is the most widely accepted (Jombo et al, 2017). According to the "phytasephytate-pectin" theory, water-soluble pectin permits water uptake by legume seeds.…”
Section: Storagementioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon might be attributed to hard-to-cook defect (Coelho et al, 2007;Jombo, Minnaar, & Taylor, 2017;Martín-Cabrejas et al, 1997). Several theories have been proposed to explain the hard-to-cook phenomenon, including phytase-phytate-pectin theory, lignification theory, protein and starch interactions, and a multiple mechanism theory, but the "phytase-phytate-pectin" theory is the most widely accepted (Jombo et al, 2017). According to the "phytasephytate-pectin" theory, water-soluble pectin permits water uptake by legume seeds.…”
Section: Storagementioning
confidence: 99%
“…() reported that the TPC of different pinto bean genotypes varied during storage, and the kaempferol content of CDC Pentium cultivar seed coats was reduced by almost half, whereas the kaempferol content of 1533‐15 cultivar seed coats did not change significantly. This phenomenon might be attributed to hard‐to‐cook defect (Coelho et al., ; Jombo, Minnaar, & Taylor, ; Martín‐Cabrejas et al., ). Several theories have been proposed to explain the hard‐to‐cook phenomenon, including phytase–phytate–pectin theory, lignification theory, protein and starch interactions, and a multiple mechanism theory, but the “phytase–phytate–pectin” theory is the most widely accepted (Jombo et al., ).…”
Section: Factors Influencing Phenolic Content and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of both defects in pulses can be hereditary, that is, dependent on variety/cultivar as demonstrated for beans (Njoroge et al., ; Nyakuni et al., ), cowpeas (Jombo, Minnaar, & Taylor, ), and chickpeas (Reyes‐Moreno, Okamura‐Esparza, Armienta‐Rodelo, Gomez‐Garza, & Milan‐Carrillo, ). It can also be dependent on seed size, with smaller seeds being more prone to HTC as demonstrated for beans (De J. Berrios, Swanson, & Cheong, ; Nyakuni et al., ).…”
Section: Defects That Influence Soaking and Cooking Of Pulsesmentioning
confidence: 99%
“…In addition, phytic acid content was related to susceptibility to HTC development in chickpeas (Reyes-Moreno et al, 2000) but not in beans (Martin-Cabrejas, Esteban, Perez, Maina, & Waldron, 1997). Irradiation of HTC cowpeas leading to reduced cooking time was associated with changes in pectin solubility (Jombo et al, 2018).…”
Section: Hypotheses For Hardening Of Pulses: Current Insightsmentioning
confidence: 99%